Dermatoscopic findings of urticaria pigmentosa - Miller, Marcela Duarte Benez (Sociedade Brasileira de Dermatologia, 2013)

(untitled)
Mastocytosis is a rare disease characterized by proliferation and accumulation of mast cells in various organs. The maculopapular cutaneus mastocytosis is divided into three subtypes: papular/plaque variant, urticaria pigmentosa and eruptive macular telangiectasia perstans. Dermoscopic may help to better characterize the different forms of cutaneus mastocytosis. We report a 55 year-old female with urticaria pigmentosa and its dermoscopy.